The impact of microscopic extrathyroidal extension on the prognosis of medullary thyroid carcinoma: A multicenter cohort study - Ozturk, Beyza Olcay; Keskin, Umran; Uysal, Serhat; Hacioglu, Aysa; Karsli, Seda; Andac, Burak; Zuhur, Sayid Shafi (Elsevier, 2025)
Purpose: Despite several factors are associated with worse disease-free survival (DFS) and prognosis in medullary thyroid carcinoma (MTC) patients, the effect of microscopic extrathyroidal extension (mETE) on the prognosis and DFS is not well understood. This study aims to evaluate the impact of mETE on DFS and prognosis in patients with MTC. Methods: This multicenter study included 208 patients with MTC (17.8% with hereditary disease). Patients with mETE were compared to those without mETE in terms of clinical and histopathological variables. Results: Among the 208 patients, 16.3% (n = 34) had mETE on histopathological analysis. Patients with mETE were more likely to have larger tumors, higher serum calcitonin (CTN) levels before and after surgery, increased rates of neck lymph node (LN) and distant metastasis, multifocal disease, and advanced disease stage. Kaplan-Meier analysis showed a significantly lower DFS in patients with mETE than those without mETE (14.7% vs. 71.3%, log-rank p < 0.001). However, mETE was not an independent contributing factor for persistent/recurrent disease, whereas neck LN involvement was the strongest independent contributing factor for persistent/recurrent disease (HR: 1.1; 95% CI 0.4-1.8, p = 0.76 and HR: 9.6; 95%CI 1.21-76.9, p = 0.03, respectively). Conclusion: mETE in patients with MTC is associated with a lower DFS, larger tumor sizes, a higher likelihood of neck LN and distant metastasis, advanced stage, higher serum CTN levels, multifocality, and persistent/recurrent disease. However, mETE was not an independent predictor of persistent/recurrent disease. Further studies with a larger number of patients with mETE could further clarify the impact of mETE on the prognosis of MTC. (c) 2025 SEEN and SED. Published by Elsevier Espana, S.L.U. All rights are reserved, including those for text and data mining, AI training, and similar technologies.
El impacto de la extensión microscópica extratiroidea en el pronóstico del carcinoma medular de tiroides: un estudio de cohorte multicéntrico
Keywords: Medullary thyroid cancer; Microscopic extrathyroidal extension; Disease-free survival